Fatigue Behavior Analysis and Life Prediction of Overhead Conductors Subject to Narrowband Vibration - Ferreira, Jorge; Badibanga, Remy; Araujo, Jose Alexander; Silva, Cosme (IEEE transactions on power delivery, 2023)
This paper aims to present a contribution to the study of the effect of random vibration on the useful life of overhead conductors. This study compares two approaches based on an acquired vibration signal. The first one is the time-domain approach (based on rainflow cycle counting), while the second one is the frequency-domain approach (based on power spectral density moments). Laboratory simulation of aeolian vibration was used in finding the fatigue characteristics of a ACSR 397,5MCM - IBIS conductor. The S-N diagram was generated by performing 9 fatigue tests under constant amplitude conditions and 13 fatigue tests in narrowband excitation conditions. The reported tests were performed to assess the effect of random loading on fatigue life considering the two approaches for estimating fatigue life. A good correlation was found between the estimated fatigue lives using the time-domain and frequency-domain approaches and the experimental data..